THE PATTERN OF DRUG USES IN PREGNANT WOMEN ATTENDING THE ANTENATAL CLINIC OF THE OBSTETRICS AND GYNAECOLOGY DEPARTMENT AT A TERTIARY CARE HOSPITAL - CHAURASIYA, VIDYABRAT RAKESH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the study was to study and evaluate the pattern of drug use in pregnant women attending the antenatal clinic of obstetrics and gynaecology department at a tertiary care hospital. Methods: A prospective observational study was conducted at the Department of Gynecology and Obstetrics in M.G.M. Medical College and Hospital, Kishanganj, Bihar. The study included 368 pregnant women who consented and provided written informed consent for participation in this study during the study period from January 2020 to November 2021. Results: Time for seeking the first antenatal check-up was majorly in 1st trimester (48.10%), followed by 35.60% in the 2nd and 16.30% in the 3rd trimester. A total of 3054 drugs were prescribed in all three trimesters from all organ systems. The majority belonged to blood and bone-forming agents, followed by antimicrobials and gastrointestinal drugs. Analyzing the prescribing trend grossly depicts that the drug prescribing showed a gradual increase from 18 to 2nd trimester, followed by a slow drop in 3rd trimester. During the entire study period, there were 177 prescriptions for 1st trimester, 306 prescriptions for 2nd trimester, and 366 prescriptions for 3rd trimester. Conclusion: Our study site revealed a greater tendency to prescribe by generic name rather than by brand name in our hospital, which is a good sign as it reduces the economic burden on the patients. In other previous studies, it was less. Prescribing percentage of antibiotics in all trimesters was on the high rise, while the percentage of encounters with injection was within acceptable ranges. The majority of prescribing corroborated with national drug policy and was in concurrence with the national drug formulary and NLEM 2015, which reflects the essence of rational prescribing of pregnancy drugs in our set-up.